BAM15‐mediated mitochondrial uncoupling protects against obesity and improves glycemic control. Issue 7 (10th June 2020) - Axelrod, Christopher L; King, William T; Davuluri, Gangarao; Noland, Robert C; Hall, Jacob; Hull, Michaela; Dantas, Wagner S; Zunica, Elizabeth RM; Alexopoulos, Stephanie J; Hoehn, Kyle L; Langohr, Ingeborg; Stadler, Krisztian; et al.
Abstract: Obesity is a leading cause of preventable death worldwide. Despite this, current strategies for the treatment of obesity remain ineffective at achieving long‐term weight control. This is due, in part, to difficulties in identifying tolerable and efficacious small molecules or biologics capable of regulating systemic nutrient homeostasis. Here, we demonstrate that BAM15, a mitochondrially targeted small molecule protonophore, stimulates energy expenditure and glucose and lipid metabolism to protect against diet‐induced obesity. Exposure to BAM15 in vitro enhanced mitochondrial respiratory kinetics, improved insulin action, and stimulated nutrient uptake by sustained activation of AMPK. C57BL/6J mice treated with BAM15 were resistant to weight gain. Furthermore, BAM15‐treated mice exhibited improved body composition and glycemic control independent of weight loss, effects attributable to drug targeting of lipid‐rich tissues. We provide the first phenotypic characterization and demonstration of pre‐clinical efficacy for BAM15 as a pharmacological approach for the treatment of obesity and related diseases. Synopsis: This study presents a novel therapy for treatment of obesity‐related diseases. Oral delivery of the mitochondrial protonophore BAM15 markedly reduced weight gain and fat accrual while improving glycemic control. BAM15 displays extended mitochondrial activity compared to previous generation protonophores. BAM15 protects against diet induced obesity. BAM15 modulates body composition and glycemic control independently of its weight‐reducing effects. AMPK is required to sustain the metabolic benefit of BAM15, which occurs primarily in adipose tissue. Abstract : This study presents a novel therapy for treatment of obesity‐related diseases. Oral delivery of the mitochondrial protonophore BAM15 markedly reduced weight gain and fat accrual while improving glycemic control.